The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3390/ijerph8030648
|View full text |Cite
|
Sign up to set email alerts
|

Recent Contributions of Air- and Biomarkers to the Control of Secondhand Smoke (SHS): A Review

Abstract: Since the publication of the US Surgeon General Reports in 1996 and 2006 and the report of the California Environmental Protection Agency in 1999, many reports have appeared on the contribution of air and biomarkers to different facets of the secondhand smoke (SHS) issue, which are the targets of this review. These recent studies have allowed earlier epidemiological surveys to be biologically validated, and their plausibility demonstrated, quantified the levels of exposure to SHS before the bans in various env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 128 publications
1
7
0
1
Order By: Relevance
“…The suggestive dose–response relationship between heavier smoking and infertility found in our analysis are similar to measures of association found in another large prospective cohort study 3. Associations between SHS and infertility have been studied since the 1980's with mixed results, perhaps due to small sample sizes and/or methodological limitations 7 16 18–24 43. Using data from a large prospective cohort, our study adds to the evidence base by demonstrating significant associations between the highest SHS exposure during reproductive life and delayed conception.…”
Section: Discussionsupporting
confidence: 85%
“…The suggestive dose–response relationship between heavier smoking and infertility found in our analysis are similar to measures of association found in another large prospective cohort study 3. Associations between SHS and infertility have been studied since the 1980's with mixed results, perhaps due to small sample sizes and/or methodological limitations 7 16 18–24 43. Using data from a large prospective cohort, our study adds to the evidence base by demonstrating significant associations between the highest SHS exposure during reproductive life and delayed conception.…”
Section: Discussionsupporting
confidence: 85%
“…Smoking cessation by parents and other caregivers is the best way to protect children from ETS exposure at home [ 36 ]. The self-reported 7-day quit rate in the intervention group in our study was higher than the reported quit rates in a randomized controlled trial (Hong Kong) [ 37 ], but lower than Krieger et al .’s study also in the US [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The private domain is now the main location of exposure to SHS for children,42 but reducing exposure in this domain is more difficult to influence. Previous work in the USA has shown that feedback of information on airborne nicotine levels may be useful in changing smoking behaviour of parents who smoke,27 while a recent study has looked at the use of air-filtration systems to reduce children's exposure at home 43.…”
Section: Discussionmentioning
confidence: 99%